Basket clinical trial design for targeted therapies for cancer: a French National Authority for Health statement for health technology assessment. Issue 10 (October 2021) - Lengliné, Etienne; Peron, Julien; Vanier, Antoine; Gueyffier, François; Kouzan, Serge; Dufour, Patrick; Guillot, Bernard; Blondon, Hugues; Clanet, Michel; Cochat, Pierre; Degos, Françoise; Chevret, Sylvie; et al.
Summary: During the past decade, health technology assessment bodies have faced new challenges in establishing the benefits of new drugs for individuals and health-care systems. A topic of increasing importance to the field of oncology is the so-called agnostic regulatory approval of targeted therapies for cancer (independent of tumour location and histology) granted on the basis of basket trials. Basket trials in oncology offer the advantage of simultaneously evaluating treatments for multiple tumours, even rare cancers, in a single clinical trial. To address the novel challenges introduced by these trials, an interdisciplinary panel was convened on behalf of the Transparency Committee of the French National Authority for Health to clarify an approach designed to guarantee a transparent, reproducible, and fair assessment of histology-agnostic treatments for reimbursement by the French National Health Insurance Fund. The requirements of this approach include the need for randomisation, clinically relevant endpoints, appropriate correction for multiple significance testing, characterisation of subgroup heterogeneity, and validation of underlying biomarker assays. A prospectively designated external control is encouraged when the implementation of a direct comparison is deemed infeasible. We also underline the importance of recording outcomes from basket trials in a registry for use as future external controls.